Optimizing the Maastricht Work-Related Support intervention in clinical patient care: the value of integrating action research into intervention mapping - Maarten Butink; Shari Hooper; Annelies Boonen; Vera Baadjou; Tim Boymans; Marieke Pierik; Angelique de Rijk (BMC, 2024)
Abstract Background Healthcare professionals (HCPs) are increasingly recommended to play an important role in supporting people with chronic disease in work participation. An intervention for HCPs to provide work-related support to their patients in clinical care was developed with intervention mapping (Maastricht Work-Related Support; Maastricht WRS). Action research proposes 'combining research and practice', which allows us to incorporate experiences of HCPs while implementing and to realize intervention's full potential. Therefore, the aim of this study is to explore, by integrating action research into an intervention mapping approach, how experiences of HCPs with early implementation can be used to optimize the Maastricht WRS in clinical care. Methods Semi-structured interviews were held with nine HCPs (response rate 82%), involved in care for people with inflammatory arthritis, knee problems or inflammatory bowel disease. Some of them were not yet trained in the Maastricht WRS while others had received the training and were providing the Maastricht WRS. Results All participants regarded WRS an important part of clinical care. Untrained HCPs indicated a lack of knowledge and skills in providing the Maastricht WRS, and a need for tools. Trained HCPs were satisfied with the training and tools, but stressed that practical limitations hindered providing the Maastricht WRS. Action research showed that the intervention meets the needs of HCPs, but need some optimizations: (1) organizing 'intervision' for HCPs, (2) inform and activate patients to discuss work with their HCP, (3) update initial tools and (4) including patients' work status in the electronic patient system. Conclusions Action research integrated into intervention mapping proved to improve the Maastricht WRS intervention. By involving HCPs, the intervention could be optimized to provide to support people with chronic diseases in clinical care in healthy and sustainable work participation.